Effects of monoclonal antibody daratumumab combined with ixazomib-based treatment regimen on survival of patients with relapsed/refractory multiple myeloma - Peng, Lang; He, Jiawen; Zheng, Ying; Zeng, Qingfang (Vojnosanitetski pregled, 2025)
Background/Aim. Combination therapy with daratumumab and ixazomib has been previously used for the treatment of multiple myeloma (MM), but treatment outcomes of these drugs and safety have not yet been confirmed. The aim of the study was to assess the effects of monoclonal antibody daratumumab in combination with an ixazomib-based treatment regimen on the survival of patients with relapsed/refractory MM (RRMM). Methods. A retrospective study included the clinical data of 65 RRMM patients admitted from March 2016 to March 2019. The patients were divided according to different treatment regimens into two groups: Group A, with 31 patients, treated with a combination of ixazomib, dexamethasone, lenalidomide, and Group B, with 34 patients, treated with a combination of ixazomib, dexamethasone, lenalidomide, and daratumumab. Treatment outcomes, adverse reactions, quality of life, and survival were compared. Results. Groups A and B showed no significant differences in the objective response rate (70.97% vs. 85.29%) or the type and grade of adverse reactions (p = 0.161). The scores of all dimensions of the World Health Organization Quality of Life Brief Version of group B were higher than those of group A after treatment (p < 0.05). There was no significant difference in the one-year or three-year survival rate between group A (64.52%, 19.35%) and group B (73.53%, 32.35%) (p = 0.432 and p = 0.234, respectively). Still, group B had a significantly higher two-year survival rate than that of group A (61.76% vs. 35.48%) (p = 0.034). Conclusion. The combination of daratumumab and ixazomib-based treatment regimen helps improve the survival and quality of life of RRMM patients without increasing the incidence rate of adverse reactions during treatment.